2012
DOI: 10.1155/2012/725121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surgical Technique on Mastectomy and Reexcision Rates in Breast-Conserving Therapy for Cancer

Abstract: Introduction. Breast conserving surgery (BCS) requires tumor excision with negative margins. Reexcision rates of 30–50% are reported. Ultrasound localization, intraoperative margin pathology, and specimen mammography have reduced reexcisions, but require new equipment. Cavity shave margin (CSM) is a technique, utilizing existing equipment, that potentially reduces reexcision. This study evaluates CSM reexcision impact. Methods. 522 cancers treated with BCS were reviewed. Patients underwent standard partial mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
1
17
2
Order By: Relevance
“…There are publications in the literature reporting re-excision rates in the range of 9-50% following BCS (21,22). We think that the reason why the re-excision rate of 4% in our series was lower as compared to similar publications was that the number of our cases was low.…”
Section: Discussioncontrasting
confidence: 58%
“…There are publications in the literature reporting re-excision rates in the range of 9-50% following BCS (21,22). We think that the reason why the re-excision rate of 4% in our series was lower as compared to similar publications was that the number of our cases was low.…”
Section: Discussioncontrasting
confidence: 58%
“…The association of positive surgical margins after lumpectomy with lobular histology, multifocality, lymphovascular invasion (LVI), high grade DCIS, and an extensive intraductal component (EIC), is well reported in the literature . Others have begun to explore the role of surgical technique . This study was undertaken to further define modifiable risk factors for positive margins and residual disease following lumpectomy and to validate previous findings in our patient population.…”
mentioning
confidence: 57%
“…7 Unzeitig et al found that routine cavity shaving resulted in nearly half the reexcision rate associated with standard partial mastectomy (24% vs. 47%, P<0.001). 8 Similarly, Marudanayagam et al found that before the introduction of cavity shaving, 49 of 392 patients (12%) underwent reoperation for margin clearance, whereas afterward, only 22 of 394 patients (6%) who underwent cavity shaving required further surgery. 9 Cao et al found that 59% of 103 patients who had positive margins on their initial specimen had negative margins after cavity shaving.…”
Section: Discussionmentioning
confidence: 96%